Evaluating concepts for automated tool handling - Abbas, Hussein; Broström Vedin, Albin (My University, 2023)
Production of aircraft parts undergoes processes where tough materials are pro cessed with high-quality requirements. Today’s increased demand for production places higher demands on the tool handling that exists within these productions, which leads to the purpose of this report. The master thesis has been carried out to see if there are other methods to improve tool handling within a part of production at GKN Aerospace. The work was carried out with a background study where important data collection was acquired to then use a simulation tool to see possible results. The background study showed that automated solutions were of interest as they can increase accu racy and productivity. The execution of these months of work has led to the conclusion that automated solutions can be beneficial. The simulation has given results such as increased productivity, reduced costs, and improved ergonomics, but also how good results a simulation tool can provide to test possible and new solutions.
Keywords: Tool Management, Automation, Simulation, Aerospace Manufacturing